'Freedom From Fear and Want' and Our Psychological Response to Environmental Changes. (22nd August 2017) - Wei, Zi-Han; Tao, Rui; Liu, Huan; Li, Shu
Freedom from fear and freedom from want are two of the fundamental freedoms and likely related to changes in the environment. It has usually been assumed that our subjective feelings should change accordingly with changes in the objective environment. However, two counterintuitive effects reviewed in this article imply a rather complex psychological mechanism behind how people respond to environmental changes and strive for the freedom from fear and want. The first is the 'psychological typhoon eye' effect, in which the closer people are to hazards, the calmer they feel. Several possible explanations have been proposed, but the mechanism behind this effect remains unclear. The findings are important for future post-disaster interventions and helpful for policy makers in risk management and researchers in risk studies. The second effect is the 'town dislocation' effect, wherein although inhabitants' objective quality of life is improved during the urbanisation process, the projected endorsement and rated social ambience of town residents is lower than that of residents in the country and in the city; this effect is mediated by social support. The findings have implications for how to better assess the urbanisation process and how to improve people's affective appraisals of their living environment.